Political Parties and Their Role in Determining a Territorial Division of Poland - Słobodzian, Beata (Political Preferences, 2015)
A territorial division of a country constitutes the basis of a current organization of the communal life; hence its stability is a fundamental condition of an effective administration in a local, regional as well as statewide scale. Therefore, political parties that are involved in drafting the law as well as are entitled to accept or reject acts shall perform for the benefit of general public, but for particular reasons. Key words: territorial division, territorial structure, conception of division, political programs